COBIT 2019 foundation - Lowrie, Daniel; Ward, Chris (Packt Publishing, 2024)
The course begins with an introduction to COBIT 19, setting the stage for a comprehensive exploration of enterprise governance of information and technology. It delves into the significant benefits I&T governance brings to the table, emphasizing the importance of aligning IT processes with business goals. The course focuses on detailing what COBIT is and importantly, what it is not, establishing a clear understanding of its scope and application. Through an examination of COBIT's six principles for a governance system and its three framework principles, learners gain insights into the enhancements introduced in COBIT 2019. The course wraps up by guiding learners through the governance and management objectives, the components of the governance system, and the impactful design factors, alongside providing practical insights into the COBIT implementation guide approach. Through this journey, participants will grasp the vital role of COBIT in the IT world and prepare for what lies beyond the COBIT certification. What you will learn Understand enterprise governance of IT Navigate COBIT 2019 enhancements Identify governance and management objectives Apply COBIT in various IT scenarios Achieve COBIT certification readiness Plan for continual IT governance improvement Audience This course is ideal for IT professionals, auditors, and managers aiming to bolster their organization's IT governance. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Daniel Lowrie: Daniel Lowrie's IT career began with workstation support and Y2K compliance updates for a teaching hospital in North-Central Florida. His journey led him to become an in-classroom trainer and Mentored Learning Instructor, specializing in courses covering Microsoft Windows Desktops and Servers, Active Directory, Networking, CCNA, and Linux. He then transitioned to becoming a Systems and Network administrator for a large insurance company before joining ACI Learning as an Edutainer. Certifications: CompTIA A+, Network+, Linux+, CySA+, and PenTest+; CEH; MCSA; CFR; eJPT Chris Ward: Chris has been a Technical Instructor for 20+ years with certifications in CompTIA, Microsoft, Cisco and more. Much of his experience has been as a PMP and ITIL℗ʼ Expert/Managing Professional. Chris is a sought-after conference speaker and consultant in ITSM and a published author. Certifications: CompTIA A+, Network +, iNet+, MCSE: Communication, MCSE: Server Infrastructure, CCNP, CWLS, AWLSS, AWLDS, PMP, ITIL℗ʼ Expert v3, ITIL℗ʼ 4 Managing Professional/Strategic Leader, PRINCE2 Practitioner, COBIT 2019 Foundation.
Online resource; title from title details screen (O'Reilly, viewed March 4, 2024)
Keywords: Information technology -- Management; COBIT (Information technology management standard); Technologie de l'information; Gestion; COBIT (Norme); Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet